Advanced computational tools for PEM fuel cell design Part 1. Development and base case simulations - Sui, P.C.; Kumar, S.; Djilali, N.
This paper reports on the development and numerical implementation of a comprehensive 3D computational fuel cell dynamics code for PEMFCs. The code solves a set of coupled non-linear conservation equations (mass, momentum, species, energy, electrical potential and liquid water saturation)for an entire unit cell. A phenomenological model for water transport in the membrane is solved separately for the membrane domain, in conjunction with calculation of the water content on the boundary such that that water balance is satisfied on both sides of the membrane interface, and the numerical implementation of the model is validated against an analytical solution. The global polarization curve predicted with the CFD code is found to compare favorably with reported data. A detailed validation of the CFD code against spatially resolved experimental data is presented in a companion Part 2 paper, and in this paper base case simulations for a unit cell with straight channels are presented to illustrate and analyze basic physical features, transport of species along the channel and coupling between heat and mass transfer processes. Analysis of the results shows that many of the variables of interest, including mass fractions and current densities, exhibit similar profiles along the channel, which suggests that reduced dimensional model based on appropriate similarity variables might be suitable for rapid calculations.
Keywords: COMPUTATIONAL FLUID DYNAMICS; MODELING; MEMBRANE TRANSPORT; WATER BALANCE; CURRENT MAPPING; CAPILLARY DIFFUSIVITY